Autologous Transfusion after Total Knee Arthroplasty - Fayyaz Ahmed Orfi; Shafqat Hussain; Ramna Dilbar; Ali Arslan Munir; Sumbal Rana (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine whether the blood lost in total knee arthroplasty surgery can be salvaged and reused using the autotransfusion technique without adverse effects and need more blood requirement.